The Role of Creative Self-Efficacy on The Proactive Personality and Self- Leadership to Innovative Work Behavior Relationship - Mahardika, Ghana Yoga; Yohana, Corry; Fauzi, Achmad (Program Studi S3 Ilmu Manajemen, 2024)
This study examines the role of proactive personality (PP) and self-leadership (SL) in the innovative work behavior (IWB) of employees at the Bodhi Prasadha Foundation. In addition, the purpose of this study is to investigate the mediating effect of creative self-efficacy (CSE) on the relationship between proactive personality (PP) and self-leadership (SL) with Innovative Work Behavior (IWB) of employees at the Bodhi Prasadha Foundation. Primary data were collected from employees at the Bodhi Prasadha Foundation. Structural Equation Modeling (SEM) was used to analyze the data and identify direct and indirect effects. The findings show a significant positive impact of self-leadership (SL) on the Innovative work behavior of employees at the Bodhi Prasadha Foundation. In addition, self-leadership (SL) was found to have a direct and indirect effect on Innovative work behavior (IWB), with the indirect effect mediated by creative self-efficacy (CSE). This finding highlights the importance of having programs that help people become better at leading themselves, such as classes on how to manage one's own actions, things that make employees want to do their best, setting goals for oneself, and managing how to act. By strengthening self-leadership, companies can increase the creative confidence of their employees, which will improve IWB. Companies should not rely solely on people who are naturally ready to take on responsibility when recruiting them, as this study shows that readiness to take on responsibility does not always help in generating new ideas if there is insufficient mental and company support.